Tracking and dating incipient melting of a new grouplet of primitive achondrites. (15th March 2023) - Jiang, Yun; Li, Ye; Liu, Jia; Wang, Qing; Qin, Li-Ping; Zhu, Ke; Liao, Shiyong; Yin, Zongjun; Peng, Yongbo; Koefoed, Piers; Hsu, Weibiao 徐伟彪
Abstract: Primitive achondrites, representing 'transitional' samples between chondrites and differentiated achondrites, provide a great opportunity to decode the thermal histories of planetesimals in the early solar system. In this work, we report a comprehensive study of petrography, mineralogy, O-Cr isotopes and 53 Mn- 53 Cr systematics of four ungrouped primitive achondrites, Northwest Africa (NWA) 12869, NWA 3250, NWA 11112, and Tafassasset. High resolution X-ray tomographic microscopy (HR-XTM) observations yield the 3D spatial distributions of metal, sulfide, and plagioclase, providing the direct petrologic evidence for incipient melting. In NWA 12869, NWA 3250, and NWA 11112, only FeNi-FeS eutectic melting occurs, with small fractions of metal and sulfide melt and amalgamate sporadically. As for Tafassasset, in addition to common metal and sulfide melt, plagioclase (±pyroxene) extensively melts and interconnects to form networks, with the generation of basaltic melts. The 53 Mn- 53 Cr systematics in NWA 12869 [initial 53 Mn/ 55 Mn of (3.24 ± 0.32) × 10 −6 ] and Tafassasset [initial 53 Mn/ 55 Mn of (3.48 ± 0.20) × 10 −6 ] are determined with mineral separates and bulk samples. When anchored to the D'Orbigny angrite, NWA 12869 has a 53 Mn- 53 Cr age of 4563.4 ± 0.6 Ma, while Tafassasset has an age of 4563.8 ± 0.4 Ma. The Mn-Cr ages of NWA 12869 and Tafassasset record the time of incipient melting within their parent bodies. Considering that NWA 12869, NWA 3250, and NWA 11112 exhibit the same olivine-dominated (47–69 vol%) mineral assemblages with recrystallized textures and a great similarity in mineral chemistry (olivine: Fa35–38 ; pyroxene: Fs27–30 Wo3.0–3.5 ; plagioclase: An47–50 ; chromite: Cr#: 74–76; Mg#: 14.0–14.6), oxygen fugacity (IW-2 to IW-1), as well as 54 Cr nucleosynthetic anomalies (ε 54 Cr: 1.01 ± 0.09 to 1.44 ± 0.18) and oxygen isotopes (Δ 17 O: −1.72 to −1.78 ± 0.05‰), we first classify them into a new grouplet of primitive achondrites, different from Tafassasset. This grouplet does not share a parent body with CR chondrites, but rather derives from incipient melting of a carbonaceous chondrite parent body which formed in a nebular reservoir physically close to that sampled by CR chondrites. More chondrite, differentiated achondrite, and/or iron samples associated with this new grouplet would provide further constraints on the rate and onset time of accretion, as well as the interior structure of the planetesimal in the outer solar system.